Antimicrobial Resistance Patterns and Clonal Distribution of E. coli, Enterobacter spp. and Acinetobacter spp. Strains Isolated from Two Hospital Wastewater Plants - Miguel Galarde-López; Maria Elena Velazquez-Meza; Miriam Bobadilla-; Patricia Cornejo-Juárez; Berta Alicia Carrillo-Quiroz; Alfredo Ponce-; Alejandro Sassoé-González; Pedro Saturno-Hernández; Celia Mercedes Alpuche-Aranda (MDPI AG, 2022)
The objective of this study was to determine the presence and persistence of antimicrobial-resistant enterobacteria and their clonal distribution in hospital wastewater. A descriptive cross-sectional study was carried out in wastewater from two Mexico City tertiary level hospitals. In February and March of 2020, eight wastewater samples were collected and 26 isolates of enterobacteria were recovered, 19 (73.1%) isolates were identified as E. coli, 5 (19.2%) as Acinetobacter spp. and 2 (7.7%) as Enterobacter spp. Antimicrobial susceptibility profiles were performed using the VITEK 2® automated system and bacterial identification was performed by the Matrix-Assisted Laser Desorption/Ionization-Time of Flight mass spectrometry (MALDI-TOF MS®). ESBL genes were detected by polymerase chain reaction (PCR) and clonal distributions of isolates were determined by pulsed-field gel electrophoresis (PFGE). E. coli susceptibility to different classes of antimicrobials was analyzed and resistance was mainly detected as ESBLs and fluoroquinolones. One E. coli strain was resistant to doripenem, ertapenem, imipenem and meropenem. The analysis by PCR showed the presence of specific β-lactamases resistance genes (blaKPC, blaCTX-M). The PFGE separated the E. coli isolates into 19 different patterns (A-R). PFGE results of Acinetobacter spp. showed the presence of a majority clone A. Surveillance of antimicrobial resistance through hospital wastewater is an important tool for early detection of clonal clusters of clinically important bacteria with potential for dissemination.